A nutrition-focused review of the interventions in US-living Latino communities with type II diabetes - Guirette, Mélanie; Sevilla-Gonzalez, Magdalena; Balaguera, Maureen; Caballero, Augusto Enrique (Frontiers in Nutrition, 2024)
Type 2 diabetes (T2D) is a chronic, debilitating disease that disproportionally affects the Hispanic/Latino community residing in the United States. Optimal nutrition therapy is fundamental to the proper management of T2D and must be culturally adapted to facilitate permanent behavior change in this population. This review selected and assessed the nutrition components of interventions aimed to improve T2D outcomes in US based Latinos/Hispanics, published from 2002 to 2023. An overview of the participant characteristics, nutrition intervention, and dietary assessment and outcomes is included. Nutrition interventions in this community benefit from the inclusion of bicultural registered dietitian nutritionist (RDNs) to assure the counseling team promotes culturally tailored nutrition recommendations based on current dietary guidelines. Nutrition assessment and outcomes should be captured with the use of validated dietary assessment tools and dietary quality indices appropriate to their target population. Standardizing these practices will facilitate intervention comparability and replicability and ultimately better target the needs of this community.